2022
DOI: 10.1111/jar.13005
|View full text |Cite
|
Sign up to set email alerts
|

Electronic assistive technology use and supported employment

Abstract: Background: Level of electronic assistive technology use by people with intellectual disabilities is lower than for other disability groups.Methods: In this mixed-methods exploratory study during the pandemic, staff (online survey) and executive administration (focus group) from a regional supported employment service provider in the Midwest US were surveyed about use of and barriers to use of electronic assistive technology for their clients with intellectual disabilities.Results: Forty percent of staff repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…Research has demonstrated that AT can positively impact the work performance of PwID (Morash Macneil et al, 2018). Furthermore, it has been suggested that AT could reduce the need for dependency on others such as job coaches (Heman et al, 2022). AT, is therefore considered to be of fundamental importance for PwID as it can enhance functional abilities and independence thereby ensuring inclusion in all aspects of life including the workplace (Boot et al, 2018).…”
Section: The Role Of Assistive Technologies (Ats)mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that AT can positively impact the work performance of PwID (Morash Macneil et al, 2018). Furthermore, it has been suggested that AT could reduce the need for dependency on others such as job coaches (Heman et al, 2022). AT, is therefore considered to be of fundamental importance for PwID as it can enhance functional abilities and independence thereby ensuring inclusion in all aspects of life including the workplace (Boot et al, 2018).…”
Section: The Role Of Assistive Technologies (Ats)mentioning
confidence: 99%
“…Damianidou et al (2019) note that as more sophisticated technology becomes available on the market, the need to select AT on an individual level has become even more important. Furthermore, once the AT is identified, there may be difficulties with access to AT products due to cost and a lack of funding mechanisms (Heman et al, 2022). When AT is procured, support to learn to use the AT is required, yet this may not be available (Ward Sutton et al, 2022).…”
Section: The Role Of Assistive Technologies (Ats)mentioning
confidence: 99%
“…Ein Teil der technologiebezogenen Literatur aus der Recherche befasst sich mit digitalen Anwendungen in sozialen Organisationen, wie etwa Rehabilitationseinrichtungen. Untersucht wird beispielsweise der Einsatz von Social Media bei der Stellensuche (Garcia et al, 2016;Ipsen & Goe, 2018) oder der Einsatz von technikbasierten Kommunikationsmitteln zwischen beeinträchtigten Personen und Fachkräft en der Rehabilitation (Heman et al, 2022;Leonet & Orcasitas-Vicandi, 2021). Weiterhin werden in einigen Publikationen computergestützte Technologien oder Soft waresysteme zur Organisation von Berufsberatung, Rehabilitation und der Vermittlung von Arbeitssuchenden mit Behinderung durch Akteur:innen des VR-Systems (Gorokhov et al, 2017;Michelsen et al, 2020;Migliore et al, 2022;Truthan & Field, 2014) vorgestellt und untersucht.…”
Section: Systematisierung Der Ausgewählten Studienunclassified
“…Ein Teil der technologiebezogenen Literatur aus der Recherche befasst sich mit digitalen Anwendungen in sozialen Organisationen, wie etwa Rehabilitationseinrichtungen. Untersucht wird beispielsweise der Einsatz von Social Media bei der Stellensuche (Garcia et al, 2016;Ipsen & Goe, 2018) oder der Einsatz von technikbasierten Kommunikationsmitteln zwischen beeinträchtigten Personen und Fachkräft en der Rehabilitation (Heman et al, 2022;Leonet & Orcasitas-Vicandi, 2021). Weiterhin werden in einigen Publikationen computergestützte Technologien oder Soft waresysteme zur Organisation von Berufsberatung, Rehabilitation und der Vermittlung von Arbeitssuchenden mit Behinderung durch Akteur:innen des VR-Systems (Gorokhov et al, 2017;Michelsen et al, 2020;Migliore et al, 2022;Truthan & Field, 2014) vorgestellt und untersucht.…”
Section: Systematisierung Der Ausgewählten Studienunclassified